High-Throughput Sequence Analyses of Bacterial Communities and Multi-Mycotoxin Profiling During Processing of Different Formulations of Kunu, a Traditional Fermented Beverage - Ezekiel, Chibundu N.; Ayeni, Kolawole I.; Ezeokoli, Obinna T.; Sulyok, Michael; van Wyk, Deidre A. B.; Oyedele, Oluwawapelumi A.; Akinyemi, Oluwatosin M.; Chibuzor-Onyema, Ihuoma E.; Adeleke, Rasheed A.; Nwangburuka, Cyril C.; Hajšlová, Jana; Elliott, Christopher T.; et al. (Frontiers in Microbiology, 2019)
Kunu is a traditional fermented single or mixed cereals-based beverage popularly consumed in many parts of West Africa. Presently, the bacterial community and mycotoxin contamination profiles during processing of various kunu formulations have never been comprehensively studied. This study, therefore, investigated the bacterial community and multi-mycotoxin dynamics during the processing of three kunu formulations using high-throughput sequence analysis of partial 16S rRNA gene (hypervariable V3-V4 region) and liquid chromatography tandem mass spectrometry (LC-MS/MS), respectively. A total of 2,303 operational taxonomic units (OTUs) were obtained across six processing stages in all three kunu formulations. Principal coordinate analysis biplots of the Bray-Curtis dissimilarity between bacterial communities revealed the combined influences of formulations and processing steps. Taxonomically, OTUs spanned 13 phyla and 486 genera. Firmicutes (phylum) dominated (relative abundance) most of the processing stages, while Proteobacteria dominated the rest of the stages. Lactobacillus (genus taxa level) dominated most processing stages and the final product (kunu) of two formulations, whereas Clostridium sensu stricto (cluster 1) dominated kunu of one formulation, constituting a novel observation. We further identified Acetobacter, Propionibacterium, Gluconacetobacter and Gluconobacter previously not associated with kunu processing. Shared phylotypes between all communities were dominated by lactic acid bacteria including species of Lactobacillus , Lactococcus, Leuconostoc, Pediococcus, and Weissella. Other shared phylotypes included notable acetic acid bacteria and potential human enteric pathogens. Ten mycotoxins (3-Nitropropionic acid, aflatoxicol, aflatoxin B1 (AFB1), AFB2, AFM1, alternariol, alternariolmethylether, beauvericin, citrinin and moniliformin) were quantified at varying concentrations in ingredients for kunu processing. Except for alternariol, alternariolmethylether and beauvericin that were retained at minimal levels of < 2 μg/kg in the final product, most mycotoxins in the ingredients were not detectable after processing. In particular, mycotoxin levels were substantially reduced by fermentation, although simple dilution and sieving also contributed to mycotoxin reduction. This study reinforces the perception of kunu as a rich source of bacteria with beneficial attributes to consumer health, and provides in-depth understanding of the microbiology of kunu processing, as well as information on mycotoxin contamination and reduction during this process. These findings may aid the development of starter culture technology for safe and quality kunu production.